Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pedagang Di Pasar Seni Guwang - Mithaswari, Ida Ayu Dwi; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 2, Februari 2018 (pp. 212 - 380), 2018)
The Guwang Art Market is being abandoned due to the emergence of the modern by-market market causing the problem of declining income. This study aims to determine the effect of working capital, working hours, and location to the merchant's market revenue arts guwang either partially or simultaneously and to determine the dominant factor affecting the merchant's income. Primary data were taken with a kusioner to a sample of 85 traders in Guwang Art Market. Samples were taken by proportional stratified random sampling technique from various blocks. Data were analyzed using multiple linear regression. The result of analysis shows that working capital, working hours, and location simultaneously have a significant effect on the merchant's income. The result of t test shows that working capital has a positive and significant effect to the merchant's income. Locations have a positive and significant effect on the merchant's income While the variables of working hours have no significant effect. The dominant variable affecting the merchant's income is business capital.